Specific Waste Handling Pattern Strategies West Java Province Through The Approach In Policy Of Domestic Waste And Dangerous Toxic Materials - Rahayu, Mayang Manguri; Machrunnisa; Budiman, Johan; Hutagalung, Ira Rumiris; Andriani, Tetty (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
Domestic waste is the largest contributor to the amount according to waste criteria. So according to Law Number 18 of 2008 concerning Waste Management, household waste has special specifications in its handling patterns, the use of cleaning materials generally causes households to produce toxic and dangerous waste which is designated as specific waste. Specific waste itself is regulated in Government Regulation Number 27 of 2020 concerning Specific Waste Management. The urgency of specific household waste management is that the correlation between the two policies has not been studied. The analysis of the approaches to these two policies aims to implement the most appropriate pattern for handling domestic hazardous and toxic waste. Based on calculation results, the generation of hazardous and toxic household waste in the Regency/City of West Java Province is estimated at 416.47 tons/day and there is no special handling yet. The integrated handling pattern is still not operational because these two policies do not yet have a relationship study, because the special characteristics of these two types of waste are in contrast to their decomposition properties.